Is harbor porpoise (Phocoena phocoena) exhaled breath sampling suitable for hormonal assessments? - Reckendorf, Anja; Schmicke, Marion; Bunskoek, Paulien; Anderson Hansen, Kirstin; Thybo, Mette; Strube, Christina; Siebert, Ursula (Animals, 2021)
marine mammals, anthropogenic stressors, chemical noise pollution